The role of the electrode geometry on the dielectrophoretic assembly of multi-walled carbon nanotube bundles from aqueous solution - Abdulhameed, Abdullah; Abdul Halin, Izhal; Mohtar, Mohd Nazim; Hamidon, Mohd Nizar (Elsevier, 2022)
This paper investigates the influences of the electrode geometry in terms of shape, configuration, dimensions, overlapping, and extensions on the dielectrophoretic (DEP) assembly of multi-walled carbon nanotube (MWCNT) bundles. A computational model was employed to predict the motion, trajectory, and assembly location of MWCNT bundles. The density and shape of the assembled bundles were precisely controlled by optimizing the electrode dimensions and adjusting the AC signal parameters. Experimental work was conducted to validate the simulation results. MWCNT bundles were assembled and aligned across indium tin oxide (ITO) electrodes using an AC signal of 10 V and 1 kHz.